Ergogenic effects of caffeine are mediated by myokines - Takada, Shingo; Fumoto, Yoshizuki; Kinugawa, Shintaro (Frontiers in Sports and Active Living, 2022)
Exercise has long been known to effectively improve and enhance skeletal muscle function and performance. The favorable effects of exercise on remote organs other than skeletal muscle are well known, but the underlying mechanism has remained elusive. Recent studies have indicated that skeletal muscle not only enables body movement, but also contributes to body homeostasis and the systemic stress response via the expression and/or secretion of cytokines (so-called myokines). Not only the induction of muscle contraction itself, but also changes in intracellular calcium concentration ([Ca2+]i) have been suggested to be involved in myokine production and secretion. Caffeine is widely known as a Ca2+ ionophore, which improves skeletal muscle function and exercise performance (i.e., an “ergogenic aid”). Interestingly, some studies reported that caffeine or an increase in [Ca2+]i enhances the expression and/or secretion of myokines. In this review, we discuss the association between caffeine as an ergogenic aid and myokine regulation.